Somatostatin Treatment for Ectopic ACTH Syndrome due to Pancreatic Neuroendocrine Tumors: Review of the Literature - Da Zhang; Lin Lu; Hui-Juan Zhu; Yu Xiao; Xian-Lin Han; Shun-Da Du; Hua-Dan Xue; Qing-Xing Liu; Zhao-Hui Zhu; Ming-Ming Hu; Xiao Zhai; Xiao-Ping Xing; et al. (International Journal of Endocrinology)
Objectives. To analyze and summarize the effect of SSA treatment on EAS due to p-NETs (EAS-p-NETs). Methods. Thirteen patients with EAS-p-NETs treated with SSAs at our center or described in the literature were included in this study. Clinical characteristics, laboratory data, imaging studies, histopathologic results, the effect of SSA treatment, and the prognosis of these EAS-p-NET patients were evaluated. Results. Four males and 9 females with an average age of 42.9 years were included in the study. The mean duration of follow-up was 38.8 ± 28.2 months. As one of the combined treatment measures, SSAs controlled the levels of ACTH and cortisol in 9 of the 13 patients (69.2%). Partial response was observed in 3 patients (23.1%), stable disease in 2 patients (15.4%), and progressive disease in 6 patients (46.2%). The median time to tumor progression was 24 months, and the median overall survival was 61 months. The side effects of SSA treatment included temporary mild abdominal pain, diarrhea, gallstones, and cholecystitis. Conclusions. As a supplemental therapy, SSA treatment led to clinical and biochemical improvement with a good safety profile in patients exhibiting EAS-p-NET with metastasis. However, tumor progression was inhibited by SSA treatment in only a few patients. Combined with other treatments, SSAs may improve the prognosis of patients with EAS-p-NETs.